2010
DOI: 10.3390/polym3010010
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking the Nanostructure of Bone: Comparison of Polymeric Process-Directing Agents

Abstract: The nanostructure of bone has been replicated using a polymer-induced liquid-precursor (PILP) mineralization process. This polymer-mediated crystallization process yields intrafibrillar mineralization of collagen with uniaxially-oriented hydroxyapatite crystals. The process-directing agent, an anionic polymer which we propose mimics the acidic non-collagenous proteins associated with bone formation, sequesters calcium and phosphate ions to form amorphous precursor droplets that can infiltrate the interstices o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
121
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 43 publications
9
121
0
2
Order By: Relevance
“…The biomimetic mineralization through this process is called intrafibrillar mineralization. 8,9,14,[25][26][27] In contrast to the classical crystallization pathways, the nonclassical crystallization route involves mesoscopic transformations of self-assembled, metastable, or amorphous precursor particles into nanoparticulate superstructures. 28,29 Because this process assembles materials from the nanoscopic scale to large sizes, it is also called the bottom-up strategy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomimetic mineralization through this process is called intrafibrillar mineralization. 8,9,14,[25][26][27] In contrast to the classical crystallization pathways, the nonclassical crystallization route involves mesoscopic transformations of self-assembled, metastable, or amorphous precursor particles into nanoparticulate superstructures. 28,29 Because this process assembles materials from the nanoscopic scale to large sizes, it is also called the bottom-up strategy.…”
Section: Introductionmentioning
confidence: 99%
“…[35][36][37][38] The minor phase formed in this process is composed of metastable, amorphous, liquid-phase nanodroplets, which are the precursors of ACP. 25 It has been proposed that these precursors can be drawn into the interstices of the collagen fibrils by capillary forces of fluidic nature. Subsequently, due to the transformation of ACP to HA, collagen fibrils are embedded with HA nanocrystals similar to the natural bone structure.…”
Section: Introductionmentioning
confidence: 99%
“…Yamane, et al showed that cholesterol-bearing pullulan and mannan nanogels favor the formation of amorphous calcium phosphate (ACP) or HAP, depending on the calcium precursor concentration initially present in the reaction mixture [19]. Dogan and Öner [20] and Thula, et al [21] found strong effects of carboxylmethyl inulin (CMI), a biodegradable and non-toxic polysaccharide-based polycarboxylate, on the nucleation and growth of HAP.…”
Section: Introductionmentioning
confidence: 99%
“…Ability of HAp to remove cations such as cadmium [22], lead [22][23], copper [22], zinc [24], magnesium [24], strontium [23], lanthanum, Europium [25],vanadium [26], iron and anions carbonate and fluoride [27] are well recognized and many mechanisms have been suggested for its action. Hydroxyapatite nanocrystals can be synthesized via numerous synthetic routes, using a range of different reactants, such as Wet chemical methods precipitation [28][29][30][31][32][33] Sol Gel method [34][35][36][37] hydrothermal techniques [38][39][40][41][42] biomimetic deposition [35,[43][44] and electro deposition [45]. As far as the synthesis of HAp is concerned the properties of the final product is highly variable depending on the method of synthesis [38] .…”
Section: Introductionmentioning
confidence: 99%